If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + ax = 18 + -1bx Solving 5 + ax = 18 + -1bx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + ax = 18 + -5 + -1bx Combine like terms: 5 + -5 = 0 0 + ax = 18 + -5 + -1bx ax = 18 + -5 + -1bx Combine like terms: 18 + -5 = 13 ax = 13 + -1bx Divide each side by 'x'. a = 13x-1 + -1b Simplifying a = 13x-1 + -1b Reorder the terms: a = -1b + 13x-1
| -5x+12=3 | | 3(2m-8)=11m-18(m-3) | | 5(12-3m)=15m+60 | | 5x-3x-27=17 | | 3ab^2= | | -5x-11=6(2x-10) | | 6y-7x=13 | | 6y-8=2y+16+8y | | 2x+3y=15222 | | (3x-4)(5x+10)= | | 5y-(2y+3)=12 | | (5x+4y)=(5x-20) | | 2x+20=3x-5 | | 3(-4c+1)=5c+2+3 | | 15(x)=30 | | 2(3x-7)=4x+3 | | (3x+8)=(5x+4y) | | -2x+7x-52=13 | | 4x=63 | | 8-2y=3y+2 | | 2sec^2(2x+4)=0 | | 8x-5=-2x+15 | | 8p-3p=55 | | 175m-53625=55275-175 | | (4x+1)(5x-2)=y | | 12+7x= | | 3x+4x=4-18 | | 20=0.15A | | 6x^4-17x^2-5=0 | | 27=6-x | | (4.5)(3.75)-7=-4 | | 3/10x=24 |